Congenital self-healing reticulohistiocytosis (Hashimoto-Pritzker syndrome) - Ali M. Al Ameer; Abdullah Al Salman; Yosif Al Marzoq; Abdulmohsin Al Hajri; Ibraheem Al Omran; Salha Al Dossari; Mariam Imran (Wolters Kluwer Medknow Publications, 2015)
A case of congenital self-healing reticulohistiocytosis in an otherwise healthy newborn boy is presented. Erythematous papules covered by scales on the groin and single nodule on the left side of the forehead, which disappeared spontaneously within four months. Clinical features, histological and immunohistochemical findings are described. Up to our knowledge this is the first case described in Saudi Arabia.